2013
DOI: 10.1139/cjes-2012-0098
|View full text |Cite
|
Sign up to set email alerts
|

Scolosaurus cutleri (Ornithischia: Ankylosauria) from the Upper Cretaceous Dinosaur Park Formation of Alberta, Canada

Abstract: The synonymy of the ankylosaurid dinosaur Scolosaurus with Euoplocephalus has been widely accepted since the 1970s. However, Scolosaurus cutleri exhibits differences which separate it from Euoplocephalus tutus and Dyoplosaurus acutosquameus. Although the holotype of Euoplocephalus is fragmentary, several other specimens can be reliably referred to this taxon and thus used for comparison. Scolosaurus differs from Euoplocephalus in cervical half-ring, osteoderm, and forelimb morphology. Scolosaurus differs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 22 publications
4
32
0
1
Order By: Relevance
“…The two cervical half-rings of the North American ankylosaur Scolosaurus cutleri (Fig. 6B, 6C) are very different from Euoplocephalus (Penkalski and Blows, 2013). Scolosaurus half-rings have cranio-caudally broader basal bones with two dorsally mounted osteoderms which appear rounded in shape with low peaks, in particular in half-ring 2 (Fig, 6C) which is similar to Fig.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The two cervical half-rings of the North American ankylosaur Scolosaurus cutleri (Fig. 6B, 6C) are very different from Euoplocephalus (Penkalski and Blows, 2013). Scolosaurus half-rings have cranio-caudally broader basal bones with two dorsally mounted osteoderms which appear rounded in shape with low peaks, in particular in half-ring 2 (Fig, 6C) which is similar to Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Between the half-rings, and particularly between half-ring 1 and the skull, were bands of skin with very small granular armour, often called ossicles, which allowed flexibility of the neck, as seen in the two specimens with in situ armour, i.e. the nodosaurid Edmontonia rugosidens (AMNH P a g e | 7 5665) (Matthew 1922) and the ankylosaurid Scolosaurus cutleri (NHMUK R5161) (Penkalski and Blows, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. Arbour and P. J. Currie cervical half rings. Penkalski & Blows (2013) also provided a reassessment of Scolosaurus and argued for its distinctiveness from Euoplocephalus.…”
Section: Scolosaurus Cutlerimentioning
confidence: 99%
“…then reinstated Dyoplosaurus based on differences between that holotype (ROM 784) and material referred to Euoplocephalus. Dyoplosaurus has since been accepted as a valid taxon (Thompson et al 2012), and Scolosaurus is valid, too (Penkalski and Blows 2013). Moreover, Arbour (2010) concluded that Anodontosaurus is distinct as well, and Arbour and Currie (2013) formally reinstated it.…”
Section: Introductionmentioning
confidence: 99%